Networks, crowds, and markets reasoning about a highly connected world - Easley, David; Kleinberg, Jon. (New York Cambridge University Press, 2010)
"Over the past decade there has been a growing public fascination with the complex connectedness of modern society. This connectedness is found in many incarnations: in the rapid growth of the Internet, in the ease with which global communication takes place, and in the ability of news and information as well as epidemics and financial crises to spread with surprising speed and intensity. These are phenomena that involve networks, incentives, and the aggregate behavior of groups of people; they are based on the links that connect us and the ways in which our decisions can have subtle consequences for others. This introductory undergraduate textbook takes an interdisciplinary look at economics, sociology, computing and information science, and applied mathematics to understand networks and behavior. It describes the emerging field of study that is growing at the interface of these areas, addressing fundamental questions about how the social, economic, and technological worlds are connected"--Provided by publisher.
Machine generated contents note: 1. Overview; Part I. Graph Theory and Social Networks: 2. Graphs; 3. Strong and weak ties; 4. Networks in their surrounding contexts; 5. Positive and negative relationships; Part II. Game Theory: 6. Games; 7. Evolutionary game theory; 8. Modeling network traffic using game theory; 9. Auctions; Part III. Markets and Strategic Interaction in Networks: 10. Matching markets; 11. Network models of markets with intermediaries; 12. Bargaining and power in networks; Part IV. Information Networks and the World Wide Web: 13. The structure of the Web; 14. Link analysis and Web search; 15. Sponsored search markets; Part V. Network Dynamics: Population Models: 16. Information cascades; 17. Network effects; 18. Power laws and rich-get-richer phenomena; Part VI. Network Dynamics: Structural Models: 19. Cascading behavior in networks; 20. The small-world phenomenon; 21. Epidemics; Part VII. Institutions and Aggregate Behavior: 22. Markets and information; 23. Voting; 24. Property.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Information society; Telecommunication -- Social aspects